Chinese remainder Theorem based centralised group key management for secure multicast communication. Issue 3 (1st May 2014) - Vijayakumar, Pandi; Bose, Sudan; Kannan, Arputharaj
Abstract : Designing a centralised group key management with minimal computation complexity to support dynamic secure multicast communication is a challenging issue in secure multimedia multicast. In this study, the authors propose a Chinese remainder theorem‐based group key management scheme that drastically reduces computation complexity of the key server. The computation complexity of key server is reduced to O (1) in this proposed algorithm. Moreover, the computation complexity of group member is also minimised by performing one modulo division operation when a user join or leave operation is performed in a multicast group. The proposed algorithm has been implemented and tested using a key‐star‐based key management scheme and has been observed that this proposed algorithm reduces the computation complexity significantly.